Mitochondrial reticulum network dynamics in relation to oxidative stress, redox regulation, and hypoxia - Jezek, Petr; Plecitá-Hlavatá, Lydie (The international journal of biochemistry & cell biology, 2009)
A single mitochondrial network in the cell undergoes constant fission and fusion primarily depending on the local GTP gradients and the mitochondrial energetics. Here we overview the main properties and regulation of pro-fusion and pro-fission mitodynamins, i.e. dynamins-related GTPases responsible for mitochondrial shape-forming, such as pro-fusion mitofusins MFN1, MFN2, and the inner membrane-residing long OPA1 isoforms, and pro-fission mitodynamins FIS1, MFF, and DRP1 multimers required for scission. Notably, the OPA1 cleavage into non-functional short isoforms at a diminished ATP level (collapsed membrane potential) and the DRP1 recruitment upon phosphorylation by various kinases are overviewed. Possible responses of mitodynamins to the oxidative stress, hypoxia, and concomitant mtDNA mutations are also discussed. We hypothesize that the increased GTP formation within the Krebs cycle followed by the GTP export via the ADP/ATP carrier shift the balance between fission and fusion towards fusion by activating the GTPase domain of OPA1 located in the peripheral intermembrane space (PIMS). Since the protein milieu of PIMS is kept at the prevailing oxidized redox potential by the TOM, MIA40 and ALR/Erv1 import-redox trapping system, redox regulations shift the protein environment of PIMS to a more reduced state due to the higher substrate load and increased respiration. A higher cytochrome c turnover rate may prevent electron transfer from ALR/Erv1 to cytochrome c. Nevertheless, the putative links between the mitodynamin responses, mitochondrial morphology and the changes in the mitochondrial bioenergetics, superoxide production, and hypoxia are yet to be elucidated, including the precise basis for signaling by the mitochondrion-derived vesicles.
Keywords: mitochondriální DNA; oxidační stres; DNA, Mitochondrial; Mitochondria; hypoxie buňky; Male; reaktivní formy kyslíku; mužské pohlaví; Models, Biological; oxidace-redukce; Reactive Oxygen Species; Animals; lidé; biologické modely; ženské pohlaví; Cell Hypoxia; Humans; zvířata; Oxidation-Reduction; Female; Oxidative Stress; mitochondrie